Emotional appeal in advertising / Izz Dania Dzulkifle - Dzulkifle, Izz Dania (Faculty of Art and Design, 2020)
Emotional attraction is a very effective method of advertising. The target audience must be everyone who has feelings. This marketing method is used to promote the product for consumers. Emotional attraction in the form of advertising also enables people to react or to buy. Brands within a company need to know who their product is, and marketing teams need to understand what their users expect and want. To use short story techniques, they will make their potential clients feel and place themselves in the video, for example, ads on Thai commercial TV have captured the hearts of viewers with emotional videos around the world. They initially tell about the life of someone who is very emotional and then they point to their product to advertise at the same time to market their product in various forms. (OVelarde,2006) This attraction can be applied in many different scenarios in terms of product, service. and ideas. Advertising plays a huge role and affects emotions, attractiveness is a great way to use it. For example. when advertising a non-profit organization ad and looking for a humanitarian charity organization, we can use emotional appeal methods to supplement and express sad and pity emotions and encourage sad people to hurt in the video.